Employees' retention strategy on quality of work life (QWL) dimensions of private commercial banks in Bangladesh - Rahman, Mohammad Mizanur; Abdul, Mohani; Ali, Noor Azman; Ahmed, Md. Jamal Uddin; Rahman, Md. Saidur (Universiti Putra Malaysia Press, 2017)
Quality of Work Life (QWL) is a philosophy on employees' organizational life satisfaction. Retention of experienced and trained employees is a challenging task for all organizations, especially for banking organizations. This research paper aims at identifying underlying dimensions of QWL program that shape employees' retention strategy in Private Commercial Banks (PCBs) in Bangladesh. The study is mainly based on primary data obtained through a structured questionnaire on 200 employees working at PCBs. Independent and dependent variables on a five - point "Likert -Type Scale" specifies how strongly the respondents agree or disagree with statements. Several statistical tools and techniques such as descriptive analysis, Exploratory Factor Analysis (EFA), Zero Order Karl Pearson's correlation analysis and Ordinary Least Square (OLS) multiple regression analysis have been used to determine empirical findings and draw a conclusion. The findings of the study shows the effects which can impinge on employees' retention strategy with the dimensions (maintenance and supervisory) being particularly significant. The authority of PCBs in Bangladesh should address these dimensions to retain their experienced and trained employees.